The Effectiveness of Acceptance and Commitment Therapy in Cancer Patients with Depression and the Importance of Psychological Support - Jouilel, Fatimazohra; Klaina, Mekki; Ziani, Aicha (Darul Yasin Al Sys, 2025)
This study was motivated by the need to examine the psychological distress experienced by cancer patients, and to understand how the illness affects different aspects of their daily lives—particularly emotional, social, and cognitive domains. It aims to highlight the role of Acceptance and Commitment Therapy (ACT) in alleviating symptoms of depression and promoting mental well-being, while also emphasizing the importance of sustained psychological support for this vulnerable group. The study further seeks to demonstrate the effectiveness of ACT in enhancing psychological flexibility—a crucial factor in helping patients adapt to the ongoing challenges of illness—and to underscore the significance of integrated psychological interventions involving collaboration between medical and mental health professionals. To achieve these objectives, the study presents a critical review and analysis of prior research on acceptance- and mindfulness-based interventions, focusing on key theoretical concepts, outcomes, and implications for practice. The findings suggest that ACT-based programs contribute significantly to improving psychological flexibility, which, in turn, supports better emotional regulation, coping skills, and overall quality of life. Moreover, the integration of psychological therapy into cancer treatment protocols contributes to providing comprehensive support for patients and enables medical teams to effectively address the psychological and social challenges associated with the cancer experience.